The protective effect of pericytes on vascular permeability after hemorrhagic shock and their relationship with Cx43 - He, Shuangshuang; Zhang, Zisen; Peng, Xiaoyong; Wu, Yue; Zhu, Yu; Wang, Li; Zhou, Henan; Li, Tao; Liu, Liangming (Frontiers in Physiology, 2022)
Vascular hyperpermeability is one of the complications of hemorrhagic shock. Pericytes (PCs) are a group of mural cell surrounded microvessels and located at the basolateral side of endothelium. Previous studies showed that the damage of PCs participated in the occurrence of many diseases such as diabetic retinopathy, myocardial infarction, and so on. Whether PCs can protect vascular barrier function following hemorrhagic shock and the underlying mechanism is unknown. Hemorrhagic shock rat model, Cx43 VEC-specific knockdown mice and vascular endothelial cells (VECs) were used to investigate the role of PCs in vascular barrier function, and its relationship to Cx43. The results showed that following hemorrhagic shock, the amount of PCs in microvessels was significantly decreased, it was negatively associated with the increase in pulmonary and mesenteric vascular permeability. Exogenous infusion of PCs (106 cells per rat) colonized in microvessels and improved the pulmonary and mesenteric vascular barrier function. Up-regulation of Cx43 in PCs significantly increased the colonized amount of PCs in pulmonary vessels. While, down-regulation of Cx43 expression in PCs or knockout the Cx43 in VECs (Cx43 KO mice) significantly reduced the PCs colonization in pulmonary vessels in vivo and reduced the direct contact formation between PCs and VECs in vitro. It is suggested that PCs have important protective effect on vascular barrier function in pulmonary and peripheral vessels following hemorrhagic shock. Cx43 plays an important role in the colonization of exogenous PCs in microvessels. This finding provides a potential measure for the treatment of shock.